THE IMPACT OF NURSE-LED INITIATIVES IN FOSTERING NURSE-LED INNOVATION AND ENTREPRENEURSHIP - Abdullah Mohammed Alaydan, Mohammed Shaya Aldossri, Mona Mohammed Basirah, Mazeil Abdulrahman Almazeil, Saad Abdullah Almawash, Nasser Mohammed Alshami, Ibrahim Shabib Aldosari, Fadel Yahya Alfadel, Khalid Mohammed Algarni, Ali Fahed Alshahrani; Mohammed Mesnedaldosary, Bander Nader Almashari, Fares Ahmed Alameer, Abdulraoof Yasmeen Alkhalifa, Fadel Abbas Alnakhli (Chelonian Research Foundation, 2022)
Global health reform is necessary as a result of the mostly elderly population, rising prevalence of chronic illnesses, and mounting expenses. In order to fulfill these requirements, nurses are being urged to use their expertise to the maximum degree and assume important leadership positions in health policy, planning, and provision. This may include entrepreneurial or intrapreneurial positions. Despite being the biggest group of health professionals, nurses often face limitations in their range of responsibilities. Nurses have the ability to enhance health services in a manner that is both efficient and economical. However, in order to do this, it is essential that they be seen as equal collaborators in the delivery of health services. This article offers a worldwide perspective on the changing responsibilities of nursing in promoting innovation in the field of healthcare. This text provides a comprehensive account of the history of entrepreneurship and intrapreneurship. The text also covers the incorporation of a social entrepreneurship strategy in the field of nursing, the many environments for nurse entrepreneurship and intrapreneurship, and the potential consequences for both research and practice. Keywords: nursing, role of nursing, entrepreneurial, intrapreneurial, social entrepreneurship, Future of Nursing, health reform.